DYNAMICS OF THE PRO-INFLAMMATORY CYTOKINES CONTENT IN THE RAT ORAL MUCOSA IN THE INFLAMMATORY-DESTRUCTIVE LESIONS OF DIFFERENT GENESIS - Doroshenko, O.M.; Volosovets, T.M.; Doroshenko, M.V.; Yunakova, N.M.; Andrusenko, A.S. (World of Medicine and Biology, 2019)
Orthopedic treatment of removable denture structures made of polymeric materials is often accompanied by inflammatory and destructive changes in the tissues of the prosthetic bed, especially at the stages of adaptation to prosthetics. The inflammation that occurs at the same time leads to local proteolysis of proteins and the appearance of peptides, which, in turn, together with bacteria and their toxins, cause local production of proinflammatory cytokines IL-1β and FNP-α. Study of the content of proinflammatory cytokines IL-1β and FNP-α in the acute inflammation site caused by chemical (methylether of methacrylic acid), and thermal factors, and the dynamics of their content in the treatment of our proposed method. The research was conducted on 41 non-relative rats weighing 150 - 210 g. Experimental animals were divided into 3 groups: the first - control (11 rats), the rest (2 - 3 groups) - 15 experimental animals each. Inflammation in rats of experimental groups was caused by the following: in group 2 - by applying a metal rod heated to 120 ° C for 2-3 seconds. in the place of the transition fold; In group 3 - in a transitional fold a syringe was injected with 0.05 ml of 0.5% solution of methyl ester of methacrylic acid. Animals of the 2nd and 3rd groups were additionally divided into subgroups: 2nd and 3rd subgroups were not treated (negative control). Subgroups 2-b and 3-b after the action of the fluogenic agent on the ulcerous surfaces were applied by our proposed gel on the basis of myramistin and dexpanthenol 2 times a day. We found a minimal level of IL-1β and TNF -α in animals in the control group. At the same time, the level of TNF -α and IL-1β increased significantly in all experimental groups of animals. Later / 5 days / content in the lesion of IL-1β in the 2nd and 3rd groups increased slightly, remaining practically at the same level and at the 7th day, while the content of the cytokine of the TNF -α on the 5th day increased by 7 -mu - there was a significant decrease in its number in the inflammation cell compared with the first and fifth day. With the introduction of 5% MEMC solution, after 1 day, as with other types of lesions, the content of IL-1β and FNP-α in the lesion center sharply increased, while in the 5th and 7th days, these values were significantly lowered. At the same time, the level of IL-1β was higher in comparison with that for other types of lesions by almost 1.5 times, while the level of TNF -α was 1.7 times lower, which may indicate a more severe course of the pathological process. Changes in the cytokine status under the influence of 5% of the MEMC indicate that the inflammatory process in the mucous membrane of the prosthetic bed is more severe as a result of the effect of said toxicant. In order to treat inflammatory-destructive changes in experimental rats under the influence of various irritants, we used a adhesive-adaptive gel on the basis of miramistin and dexpanthenol, created by the staff of the Department of Pharmacology of the Kharkiv National Medical University and the Institute of Dentistry P. L. Shupik National Medical Academy of Postgraduate Education and approved by the Sanitary and Epidemiological Service of the Ministry of Health of Ukraine (registration number No. 05.03.02-07 / 44839). Studies have shown that the gel proposed by us significantly reduced the content of IL-1β and FNP-α in the chemical and thermal defeat of SOPR during the whole experiment. The pharmacological effect of the gel was higher in the treatment of burn ulcers compared with the treatment of ulcers of chemical origin. The gel based on dexpanthenol and myramystine, from the first day and until the end of the experiment, significantly reduced the content of proinflammatory cytokines, indicating anti-inflammatory and wound healing effects of the drug. The conducted experimental studies provide the basis for using the proposed gel on the basis of dexpanthenol and myramistin in clinical dental practice for the prevention and treatment of inflammatory and destructive lesions in the process of orthopedic treatment and adaptation to removable dentures.